Naturally Occurring Yeasts Associated with Thaumatotibia leucotreta Can Enhance the Efficacy of the Cryptophlebia Leucotreta Granulovirus - Marcel van der Merwe; Michael D. Jukes; Caroline Knox; Sean D. Moore; Martin P. Hill (Pathogens, 2023)
Yeasts associated with lepidopteran pests have been shown to play a role in their survival, development, and oviposition preference. It has been demonstrated that combining these yeasts with existing biological control agents can enhance their efficacy. The tortricid Thaumatotibia leucotreta is a phytosanitary pest in the South African citrus industry, with the baculovirus Cryptophlebia leucotreta granulovirus (CrleGV) being one of the components that can control this pest. Several yeast species were shown to be associated with T. leucotreta larvae, which affected their behaviour and development. A series of detached fruit bioassays were performed to determine whether the combination of yeast with CrleGV enhances its efficacy. These assays included determining the optimal yeast/virus ratio, testing all isolated yeast species in combination with CrleGV, and further improving yeast/virus formulation by adding an adjuvant. The optimal yeast concentration to use alongside CrleGV was determined to be 106 cells·mL−1. Pichia kluyveri, P. kudriavzevii, Kluyveromyces marxianus, and Saccharomyces cerevisiae in combination with CrleGV reduced larval survival compared to CrleGV alone. The addition of molasses and BREAK-THRU® S 240 to P. kudriavzevii and S. cerevisiae in combination with CrleGV did not notably improve their effectiveness; however, there was an observed decrease in larval survival. In future studies, field trials will be conducted with combinations of CrleGV and P. kudriavzevii or S. cerevisiae to investigate whether these laboratory findings can be replicated in orchard conditions.